Placebo Effects on Stress, but Not on Pain Reports. A Multi-Experiment Study - Vambheim, Sara Magelssen; Daniali, Hojjat; Flaten, Magne Arve (Frontiers in Psychology, 2021)
Background Contextual factors, such as participant/experimenter sex may moderate the placebo effects. We tested whether the participant and experimenter sex modulated placebo effects on experimentally induced pain and associated stress. Objective To investigate if (i) participant sex and (ii) experimenter sex influence placebo analgesia and subjective and physiological stress in two experiments employing a within-subjects and a mixed design, respectively. Placebo effects were investigated in pain reports, stress, and blood pressure. Methods Participants received painful stimulations and a placebo cream. In Experiment One (N = 59) participants underwent a placebo condition (PC) and a natural history condition (NHC) in random order. A placebo cream was applied in the PC and then the heat stimulation temperature was surreptitiously lowered. Identical stimulations were administered in the NHC, but with no cream, no information, and no lowered temperature. In Experiment Two, participants (N = 93) were randomly assigned to three groups receiving either a placebo cream with surreptitiously lowered intensity of electric stimuli (Placebo, PG), a placebo cream (Cream-Control, CCG) without changing the stimuli, or lowered intensity, but with no cream (Pain-Control, PCG) in a mixed design. All participants in both experiments received the same stimuli in the post-test as in the pre-test. Four experimenters (two females) in Experiment One, and five experimenters (two females) in Experiment Two conducted the studies. Results No placebo effect was seen on pain. However, there were placebo effects on stress, moderated by participant and experimenter sex: in Experiment One males in the PC had lower diastolic blood pressure (DBP) compared to males in the NHC. Participants in the PC had lower DBP compared to the NHC when tested by a female. In Experiment Two, participants expected more cream effectiveness when a female experimenter administered it, and reported lower stress in the PG compared to the PCG when tested by females. Conclusion Our findings highlight a distinction between placebo effects on pain and on associated stress. Secondly, female experimenters recorded lower physiological and subjective stress, higher effectiveness expectations, and lower pain from both sexes compared to male experimenters. Possible reasons for the failure to find a pain placebo effect are discussed.